PRAPERADILAN ATAS PENETAPAN TERSANGKA DILUAR KETENTUAN KUHAP - Rio Ramadhan Hutasuhut; Aryo Fadlian (JURNAL ILMIAH LIVING LAW, 2021)
The authority of the district court in examining and deciding whether or not the determination of a suspect is legal raises various pros and cons. As regulated in Article 1 Number 10 in conjunction with Article 77 KUHAP. Pre-trial is highlighted by the wider community, especially with the decision number 04/Pid.Prap/2015/PN.JKT.Sel in the case of Police Commissioner General Budi Gunawan who at that time was fighting the Corruption Eradication Commission, a commission to eradicate corruption, there were findings a new law that makes reform of the criminal procedural law process in Indonesia. The method used is using normative juridical legal source research with a literature study of statutory regulations and using the decisions of the South Jakarta District Court. The author considers the judge who decides the pretrial petition case is not an object of pretrial authority. With legal findings by judges, it is deemed necessary to discuss pretrial powers and pretrial decisions that have binding legal force so that they must be implemented.